Factors influencing excessive daytime sleepiness in adolescents - Thiago de Souza Vilela; Lia Rita Azeredo Bittencourt; Sergio Tufik; Gustavo Antonio Moreira (Elsevier, 2016)
Objective: Sleep deprivation in adolescents has lately become a health issue that tends to increase with higher stress prevalence, extenuating routines, and new technological devices that impair adolescents' bedtime. Therefore, this study aimed to assess the excessive sleepiness frequency and the factors that might be associated to it in this population. Methods: The cross-sectional study analyzed 531 adolescents aged 10-18 years old from two private schools and one public school. Five questionnaires were applied: the Cleveland Adolescent Sleepiness Questionnaire; the Sleep Disturbance Scale for Children; the Brazilian Economic Classification Criteria; the General Health and Sexual Maturation Questionnaire; and the Physical Activity Questionnaire. The statistical analyses were based on comparisons between schools and sleepiness and non-sleepiness groups, using linear correlation and logistic regression. Results: Sleep deprivation was present in 39% of the adolescents; sleep deficit was higher in private school adolescents (p < 0.001), and there was a positive correlation between age and sleep deficit (p < 0.001; r = 0.337). Logistic regression showed that older age (p = 0.002; PR: 1.21 [CI: 1.07-1.36]) and higher score level for sleep hyperhidrosis in the sleep disturbance scale (p = 0.02; PR: 1.16 [CI: 1.02-1.32]) were risk factors for worse degree of sleepiness. Conclusions: Sleep deficit appears to be a reality among adolescents; the results suggest a higher prevalence in students from private schools. Sleep deprivation is associated with older age in adolescents and possible presence of sleep disorders, such as sleep hyperhidrosis. Resumo: Objetivo: A privação de sono na adolescência é um importante problema de saúde na atualidade e só tende a se agravar com o aumento do estresse, da rotina extenuante e do advento de novos aparelhos tecnológicos que parecem refletir negativamente no início do sono em adolescentes. O estudo objetiva avaliar a frequência da sonolência excessiva e quais fatores podem estar associados à ela nesta população. Métodos: O estudo transversal avaliou 531 adolescentes de 10 a 18 anos em duas escolas de ensino privado e uma de ensino público, aplicando para cada adolescente cinco questionários: Cleveland Adolescent Sleepiness Questionnaire; Sleep Disturbance Scale for Children; Critério de Classificação Econômica Brasil; Questionário geral de saúde e maturação sexual; Questionário de atividade física. Realizou-se comparações entre as escolas e entre grupos com e sem sonolência por meio de correlação linear e regressão logística. Resultados: Observou-se privação de sono em 39% dos adolescentes, débito de sono maior para escolares do ensino privado (p < 0,001) e correlação positiva entre idade e débito do sono (p < 0,001; r = 0,337). Na regressão logística, apontou-se como fatores para pior grau de sonolência maior faixa etária dos escolares (p = 0,002; RP: 1,21[IC:1,07-1,36]) e maior escore na variável hiperidrose do sono do questionário de distúrbios do sono (p = 0,02; RP: 1,16[IC:1,02-1,32]). Conclusões: Conclui-se que o déficit de sono é uma realidade na população estudada, apresentando-se pior em escolares do ensino privado. A privação de sono está relacionada com a maior faixa etária dos adolescentes e possível presença de distúrbios do sono, como a hiperidrose do sono. Keywords: Adolescents, Sleep, Sleep deprivation, Sleepiness, Palavras-chave: Adolescentes, Sono, Privação de sono, Sonolência